Production and purification of outer membrane vesicles (OMVs) from a hypervesiculating strain of Escherichia coli (2021)
Outer membrane vesicles (OMVs) are spherical structures that contain a small fraction of the periplasm of Gram-negative bacteria, surrounded by its outer membrane. They are naturally produced and detached from the bacterial surface, participate in diverse biological processes, and are approximately 10-300 nm in diameter. Some genetically modified Gram-negative bacteria¿s ability to produce large amounts of these structures can be exploited for different applications, including biosensors, protein chips, and bioreactors. Traditionally, the main biotechnological application of OMVs has been their use as adjuvants for the development of vaccines due to their natural immunogenic characteristics. Among the most attractive applications is the encapsulation of proteins and peptides heterologously expressed in these bacteria. In this regard, OMVs can protect the expressed proteins, avoiding conformational changes responsible for loss of activity. Nevertheless, among the biggest challenges for all OMV applications are low yields, the presence of undesired macromolecules and the high purifications costs. Hence, the objective of this study was to produce green fluorescent protein (GFP) encapsulated into OMVs using Escherichia coli JC8031 transformed with pTRC99A-ssTorA-GFP, to establish the production and purification route. The obtained results allow establishing the possibility that saturation of the Tat system by the overexpression of GFP causes a low encapsulation efficiency. Moreover, the motility of JC8031 prevents the purification of OMVs by immobilization in alginate, while chromatography with a zeolite column separates OMVs from smaller particles. Therefore, it is necessary to standardize the production and use of the column in order to to apply it on a larger scale.